Penerapan PSAK 102 tentang Pembiayaan Murabahah pada Bank BNI Syariah Kantor Cabang Makassar - Ikhlas Ul Aqmal; Azwar Anwar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to find out the implementation of SFAS 102 for Murabahah financing at BNI Syariah Makassar Branch Office. Variables of this research are Murabahah financing and SFAS 102. The data source of this research is Operational Unit of BNI Syariah Makassar Branch Office, especially the Financing Administration. The data is collected by using documentation and interview techniques. This study used descriptive comporative method to describe and indicate the condition deeply the implementation of Murabahah financing BNI Syariah Makassar Branch Office. Based on the analysis there are records that should be applied in accordance with SFAS 102 but BNI Syariah Makassar Branch Office has not applied it, the records related to murabahah assets, discounts, murabahah receivables, and down payment. While the recording has been done by BNI Syariah Makassar Branch office is about the murabahah profit, deduction, and fines. The result of this research indicated that the implementation of Murabahah financing in BNI Syariah Makassar Branch Office is not suitable with SFAS 102. Keywords: Murabahah accounting, SFAS no. 102